Long‐term variations in sunspot magnetic field–area relation. Issue 1 (January 2017) - Nagovitsyn, Y. A.; Pevtsov, A. A.; Osipova, A. A.
Abstract : Background: Several recent studies indicated possible long‐term variations of physical properties of sunspots. Materials and Methods: Using observations of sunspot magnetic field strengths ( H ) from the Crimean Astrophysical Observatory and area ( S ) of sunspots from the Kislovodsk Mountain Astronomical Station of Pulkovo Observatory, we investigate the changes in the relation between H and S over the period of about two solar cycles (1994– 2013). The data were fitted by H = A + B log S, where A = (778 ± 46) and B = (778 ± 25). Results: We show that the correlation between H and S varies with the phase of solar cycle, and A coefficient decreases significantly after year 2001, while B coefficient does not change significantly. Furthermore, our data confirm the presence of two distinct populations in the distribution of sunspots (small sunspots with weaker field strength and large sunspots with stronger field). We show that the relative contribution of each component to the distribution of sunspots by their area changes with the phase of solar cycle and on longer‐than‐cycle periods. Conclusion: We interpret these changes as a signature of a long‐term (centennial) variations in the properties of sunspots.